Medical tourism: miracle or mirage? - Abd. Manaf, Noor Hazilah; Abdullah Yusof, Selamah; Zakaria, Intan Zanariah (2015)

(untitled)
Purpose – Medical tourism is a recent phenomenon that has generated much interest due to its huge economic potential. In the ASEAN region, Thailand, Malaysia and Singapore have the government machinery involved in expediting the growth of the industry. The purpose of this paper is to explore the impact of medical tourism on the healthcare delivery system of Malaysia as a destination country, with comparison made to Singapore and Thailand. Design/methodology/approach – The paper is based on a review of literature on medical tourism and secondary data obtained from government official documents. The literature is analyzed to draw out substantive issues affecting destination countries arising from the rapid growth of medical tourism. Findings – The authors argue that while patient inflow and revenue has been on the uptrend in Malaysia, the manifestation of rapid growth of the industry needs further evaluation. Malaysia still lags behind Thailand and Singapore in capitalising on the full economic potential of the industry. At the same time immediate impact such as internal brain drain has been observed. Policy framework needs reevaluation in order to assure benefits from the industry permeate all levels of society. Originality/value – This paper looks beyond marketing and motivation of medical tourism, to its socio-economic impact on Malaysia as a destination country. Policy recommendations formulated adds value to the study. Keywords – medical tourism, medical outsourcing, international medical travel, health tourism.